2015
DOI: 10.4238/2015.june.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the vaginal microbiota of healthy cattle and cattle with genital-tract disease

Abstract: ABSTRACT. The microbial community of the reproductive apparatus, when known, can provide information about the health of the host. Metagenomics has been used to characterize and obtain genetic information about microbial communities in various environments and can relate certain diseases with changes in this community composition. In this study, samples of vaginal surface mucosal secretions were collected from five healthy cows and five cows that showed symptoms of reproductive disorders. Following high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Outliers with a low sequence count and microbial diversity were removed. Mothur software (version 1.35.1; ) was then used to calculate indices of Shannon diversity and richness ( 27 ). The Ribosomal Database Project (RDP) Classifier software (version 16; ) was used to classify sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Outliers with a low sequence count and microbial diversity were removed. Mothur software (version 1.35.1; ) was then used to calculate indices of Shannon diversity and richness ( 27 ). The Ribosomal Database Project (RDP) Classifier software (version 16; ) was used to classify sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have previously described the microbiota of the cattle vagina 56 60 , skin 61 , and colostrum 62 . The microbiota determined in our study are each consistent with those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the bovine microbiota have gained importance in the last 5 years with the characterization of the microbiota of the rumen [ 21 24 ], the complete gastrointestinal tract [ 25 ], the nasopharynx [ 26 ], milk [ 27 29 ], the teat [ 30 ] and the vagina and/or uterus [ 31 34 ]. In contrast to previous studies that focused on implicating specific bacteria from bovine abortion material by bacterial culture and targeted molecular detection [ 4 , 6 , 35 38 ], we studied the total bacterial microbiota present in abortion material from cattle using a 16S rRNA amplicon sequencing approach.…”
Section: Discussionmentioning
confidence: 99%